2018
DOI: 10.1038/s41433-017-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Cataract in patients with diabetes mellitus—incidence rates in the UK and risk factors

Abstract: AimsTo analyze the risk of incident cataract (diagnosis or extraction) in patients with or without diabetes focusing on other comorbid conditions, antidiabetic drug use, and diabetes duration.MethodsThe study population comprised newly diagnosed diabetes patients (≥40 years) from the UK-based Clinical Practice Research Datalink (CPRD) between 2000 and 2015, and a random sample of the general population matched for age, sex, general practice, and year of diabetes diagnosis. We assessed cataract incidence rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
75
4
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 21 publications
(22 reference statements)
8
75
4
4
Order By: Relevance
“…By contrast, blood pressure was inconsistently associated with cataract in two observational studies. Becker et al found hypertension increased, while Tung et al found diastolic blood pressure ≥ 90 mmHg (after adjusting for blood pressure lowering medication) decreased, the odds of cataract . There was no association in the other observational studies.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…By contrast, blood pressure was inconsistently associated with cataract in two observational studies. Becker et al found hypertension increased, while Tung et al found diastolic blood pressure ≥ 90 mmHg (after adjusting for blood pressure lowering medication) decreased, the odds of cataract . There was no association in the other observational studies.…”
Section: Discussionmentioning
confidence: 95%
“…18,28,[31][32][33][34]36 The UKPDS and four observational studies showed a positive relationship with HbA 1c and one study showed a positive relationship with fasting blood glucose. 18,28,[32][33][34]36 Worse glycaemic control was associated with a higher likelihood of cataract in all but one study, the SN-DREAMS II, which found HbA 1c was protective against PSC cataracts (OR: 0.7 (95%CI: 0.5-0.9), P = 0.006). 31 A possible explanation for this unexpected finding may be the study methodology, in which participants with a different cataract and no cataract were compared with those with a specific cataract sub-type.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations